Persepsi Wartawan Perempuan Tentang Judul Berita Atlet Perempuan Pada Media Daring (Studi Deskriptif pada Wartawan Perempuan AJI Bandung) - Fuadah, Nadiana Tsamratul (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2020)
This study aims to find out how the perception of female journalists from AJI Bandung about news titles for female athletes in online media through three research focuses, namely selection, interpretation, and reaction. The research method used in this research is descriptive qualitative research method. The results showed that in the selection process, each informant had a different way. The title is one of the main ways to determine which news the informant will read. In the process of interpretation, it can be interpreted that online media makes women as objects to attract readers and the depiction of female athletes in online media should emphasize achievement more than physical. In the reaction process, the informant was dominated by anger and irritation, then the action taken by the informant after reading and interpreting the news headline about this female athlete was not to click on the news title.